Industry-Specific Factors and Retail Stores’ Financial Health: Evidence from JSE Listed Retail Stores in SADC - Nzuza, Zwelihle Wiseman; Obagbuwa, Oloyede; Rajaram, Rajendra (Journal of Ecohumanism, 2025)
This study investigates the influence of industry-specific factors on the financial health of JSE-listed retail stores in the SADC region, focusing on inventory management, operational efficiency, market share, interest rates, firm size, and leverage. Stock turnover (ST) is employed as a proxy for financial health, reflecting the ability of firms to manage resources and generate sales efficiently. Using Feasible Generalized Least Squares (FGLS) to analyse a panel dataset spanning 1994 to 2022, the findings reveal that inventory management, market share, and leverage positively and significantly impact stock turnover. Conversely, interest rates exhibit a significant negative relationship, underscoring the sensitivity of retail firms to macroeconomic conditions. The study also demonstrates the relevance of trade-off theory in explaining the relationship between leverage and financial health, emphasising the need for retail firms to balance the benefits of debt financing against its associated risks. The results provide critical insights for managers in optimising inventory management practices and capital structures to enhance financial performance. Policymakers are advised to consider the implications of interest rate fluctuations on the retail sector’s stability. Overall, the study contributes to the literature on financial health in the retail industry, offering theoretical and practical perspectives on managing industry-specific challenges.